Theater in school with or without a party will always be political - Catelan, Fernando Bueno [UNESP]; Andre, Carminda Mendes [UNESP] (Univ Estado Santa Catarina-udesc, 2019)
In Brazil, in recent years, bills based on the movement school without a party have been created and discussed in legislative houses to promote neutral education in schools and to ban any content that addresses political-party positions. However, these proposals are biased in their attempts to prohibit conversations on politics. Something that can be considered impossible, since politics is present in all our collective relations, including in schools. In this article, we observe political aspects intrinsic to school and theatrical doing. Based on Ranciere's studies on politics.
Keywords: Politics; school without party; Theater of the Oppressed